2021
DOI: 10.1097/mpg.0000000000002916
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Incidence of Isolated Biliary Atresia in Rural Areas

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Only two studies found significant seasonal variations: an increased incidence of BA from August to October in a southern US city and December to March in a southeastern US city, while the other papers did not find such seasonal variation, or at least, not any statistically significant clustering [10,11]. A recent paper from Korea which was not incorporated in the review supported clustering in summer, while on the other hand, recent results from the Netherlands, incorporating all BA cases in the country in the last three decades, did not observe any temporal clustering for isolated BA [12,13]. These contrasting results may be attributed to geographic or ethnic diversity, varying BA phenotypes, different pathogens, or other yet unknown factors.…”
Section: Seasonal Variabilitymentioning
confidence: 81%
See 2 more Smart Citations
“…Only two studies found significant seasonal variations: an increased incidence of BA from August to October in a southern US city and December to March in a southeastern US city, while the other papers did not find such seasonal variation, or at least, not any statistically significant clustering [10,11]. A recent paper from Korea which was not incorporated in the review supported clustering in summer, while on the other hand, recent results from the Netherlands, incorporating all BA cases in the country in the last three decades, did not observe any temporal clustering for isolated BA [12,13]. These contrasting results may be attributed to geographic or ethnic diversity, varying BA phenotypes, different pathogens, or other yet unknown factors.…”
Section: Seasonal Variabilitymentioning
confidence: 81%
“…These contrasting results may be attributed to geographic or ethnic diversity, varying BA phenotypes, different pathogens, or other yet unknown factors. Interestingly, a weak yet statistically significant correlation between the incidence of maternal infection at the time of conception, including Chlamydia trachomatis, and the subsequent development of BA was observed in a recent Dutch study [13].…”
Section: Seasonal Variabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…However, recently CMV+ BA has been identified as a subgroup of BA, with a poorer prognosis than IBA patients (45). Mixed results can be due to a variety of reasons, such as an immature immune system of the BA infant resulting in a lack of proof or absence of infection or that there are multiple viruses that play a role in the activation of the immune system, for example (4,46). Moreover, overactivation of the immune system that would eventually lead to BA via a virus can occur by mechanisms such as molecular mimicry or bystander activation.…”
Section: Etiology Of Biliary Atresiamentioning
confidence: 99%
“…Biliary atresia (BA) is a rare cholangiopathy of infancy leading to obliteration of the intra-and extrahepatic bile ducts (1). The incidence of BA varies around the world from 1 case per 19,000 live births in Europe to 1 per 8,000 live births in eastern Asia (2)(3)(4). Infants that are affected present with conjugated hyperbilirubinemia, acholic stools, and dark urine (5).…”
Section: Introduction Biliary Atresiamentioning
confidence: 99%